Emerging Viral Infections in Sub-Saharan Africa and the Developing Nervous System: A Mini Review - Kakooza-Mwesige, Angelina; Mohammed, Abdul H.; Kristensson, Krister; Juliano, Sharon L.; Lutwama, Julius J. (Frontiers in Neurology, 2018)
The global public health concern is heightened over the increasing number of emerging viruses, i.e. newly discovered or previously known that have expanded into new geographical zones. These viruses challenge the health care systems in sub-Saharan African (SSA) countries from which several of them have originated and been transmitted by insects world-wide. Some of these viruses are neuroinvasive, but have been relatively neglected by neuroscientists. They may provide experiments by nature to give a time window for exposure to a new virus within sizeable, previously non-infected human populations, which, for instance, enables studies on potential long-term or late-onset effects on the developing nervous system. Here we briefly summarize studies on the developing brain by West Nile, Zika and Chikungunya viruses, which are mosquito-borne and have spread world-wide out of SSA. They can all be neuroinvasive, but their effects vary from malformations caused by prenatal infections to cognitive disturbances following perinatal or later infections. We also high-light Ebola virus, which can leave surviving children with psychiatric disturbances and cause persistent infections in the non-human primate brain. Greater awareness within the neuroscience community is needed to emphasize the menace evoked by these emerging viruses to the developing brain. In particular, frontline neuroscience research should include neuropediatric follow-up studies in the field on long-term or late-onset cognitive and behavior disturbances, or neuropsychiatric disorders. Pathogenetic mechanisms for viral-induced perturbations of brain maturation, in particular during the vulnerable periods when neurocircuit formations are at peak during infancy and early childhood.